SOLID WASTE: A SOCIO-ENVIRONMENTAL MATTER - LIMA, Mirian Luiza de; RODRIGUES, Edson Vander; COSTA, Wesley Satlher da; RIBEIRO, Josimar (Revista Brasileira de Engenharia de Biossistemas, 2012)
The inappropriate treatment and disposal of municipal solid waste (MSW) have, in recent decades, exacerbated the worsening environmental problems, causing severe damage to the environment and thus reducing the quality of life. Hence the importance of educating the public and raising awareness of the need to be environmentally friendly. Thus, this paper aimed to investigate impact of MSW can generate in society. The results show that Environment Education (EE) is still lacking in the school investigated. Furthermore, it was found that 87,0 % of schools do not follow what is required by law and do not promote students awareness of selective collection, because only the Henrique Coutinho School has recycling bins.